BM-MSCs mitigate lung injury in a rat model of decompression sickness - Chen Lu; Daqian Gu; Hao Chen; Liang Chen; Jie Chen; Yuwei Weng; Xianliang Lin (PLoS ONE, 2025)
Decompression sickness is a fatal disease worldwide. Therefore, to find a prophylactic modality for decompression sickness is urgently required. Bone marrow derived mesenchymal stem cells exhibit effectiveness in antioxidant, anti-inflammation, and decrease cell death; while its effects on decompression sickness remains unclear. This study aimed to further investigate the mechanisms of decompression sickness induced lung injury, as well as effects of bone marrow derived mesenchymal stem cells on decompression sickness induced lung injury and explore the role of oxidative stress, inflammation and cell death play in this disease. The study involved Sprague-Dawley rats age at 8−10 weeks weighting 350 ± 10g. Acute lung injury was induced by decompression hyperbaric chamber. A dose of bone marrow derived mesenchymal stem cells (2 × 106 cells) was given to rats one day prior to the start of decompression. Lung injury severity was estimated by determining lung damage scores, pulmonary oxidative, inflammatory factors and cell death. In bone marrow derived mesenchymal stem cells treated rats, the morbidity and mortality of decompression markedly decreased. The increases of protein IL-1 and IL-6 in BALF and lung wet/dry ratio and lung injury score were alleviated. The ROS, CAT, SOD, and MDA activities and GSH levels were significant attenuated (P < 0.05). The pyroptosis and nerroptosis were significant mitigate (P < 0.05). Based on the results, bone marrow derived mesenchymal stem cells is an potential efficient and safe prophylactic modality protect rats from decompression induced acute lung injury.